2019
DOI: 10.1634/theoncologist.2018-0271
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Capture-Based Genomic Profiling Identifies BRAF V600 and Non-V600 Alterations in Melanoma Samples Negative by Prior Testing

Abstract: Background BRAF and MEK inhibitors are approved for BRAF V600‐mutated advanced melanoma, with response rates of up to 70%. Responses to targeted therapies have also been observed for diverse non‐V600 BRAF alterations. Thus, sensitive, accurate, and broad detection of BRAF alterations is critical to match patients with available targeted therapies. Materials and Methods Pathology reports were reviewed for 385 consecutive melanoma cases with BRAF mutations or rearrangements identified using a hybrid capture‐base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
0
5
0
1
Order By: Relevance
“…Strikingly, in the ultrarare (11, 0.15%) cases that harbored very high TMB (≥100 mut/Mb), a UV signature was usually present (77.8%, 7/9 evaluable), which suggests either an anatomic origin with exposure to solar radiation or sampling of a metastatic site with UV exposure. Interestingly, these cases also harbored frequent NF1 mutations (45.5%, 5/11) and thus, the co-occurrence of NF1 alterations and a UV signature may suggest an alternate diagnosis of desmoplastic melanoma (S100+, melanA/HMB45-negative) or radiation-associated MPNST 50 .
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Strikingly, in the ultrarare (11, 0.15%) cases that harbored very high TMB (≥100 mut/Mb), a UV signature was usually present (77.8%, 7/9 evaluable), which suggests either an anatomic origin with exposure to solar radiation or sampling of a metastatic site with UV exposure. Interestingly, these cases also harbored frequent NF1 mutations (45.5%, 5/11) and thus, the co-occurrence of NF1 alterations and a UV signature may suggest an alternate diagnosis of desmoplastic melanoma (S100+, melanA/HMB45-negative) or radiation-associated MPNST 50 .
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Ainsi, la principale difficulté de ce travail était d'évaluer de manière fiable les grades de Ceci pourrait s'expliquer par le fait que cette mutation est réputée non UV-induite, associée à un TMB plus faible, et à une moins bonne réponse à l'immunothérapie. [9,10] Avec l'avènement des thérapies ciblées et de l'immunothérapie en contexte adjuvant et néoadjuvant, le choix du meilleur traitement de première ligne va se poser pour de plus en plus de patients mutés BRAF. [11][12][13][14] Le traitement choisi doit répondre à deux exigences : un minimum de toxicité et un maximum d'efficacité.…”
Section: Discussionunclassified
“…L.Boussemart et al, in 2018 [ 26 ], tested in the interest of using Hybrid Capture-Based Genomic profiling, to identify BRAF alterations initially negative by prior BRAF classical testing. They concluded that this method should be considered, particularly in patients with initial negative result with classical methods, because of the capacity to identify more alterations in one sample, allowing personal care.…”
Section: Discussionmentioning
confidence: 99%